Economic shocks and risky sexual behaviours in low- and middle-income countries: a systematic review of the literature. Issue 2 (3rd April 2021) - Cust, Henry; Jones, Harriet; Powell-Jackson, Tim; Lépine, Aurélia; Radice, Rosalba
ABSTRACT: We document the extent to which economic shocks through economic incentives explain HIV transmission through risky sexual behaviours in LMICs. We include 35 papers containing 31 unique negative and 11 unique positive economic shocks combined with over 320 health and risky sex outcomes. We find a diverse literature with varying empirical approaches showing increases in risky sexual behaviours are more sensitive to negative shocks than decreases are to positive shocks. Those already at risk of engaging in transactional sex are particularly vulnerable to increasing risky behaviours. Protecting against negative shocks is likely to most effective in preventing HIV transmission.